MRP-WSCI: Multiple reference point based weak and strong composite indicators. - Ruiz-de-la-Rúa, Francisco; El-Gibari-Ben-Said, Samira; Cabello-González, José Manuel; Gómez-Núñez, Trinidad (Elsevier, 2019)
The construction of composite indicators is becoming an increasingly important way of managing great amounts of information obtained from multiple single indicators. Obviously, the aggregation of several indicators in a single synthetic measure always implies some loss of information on the way. For this reason, this aggregation must be done in the most informative possible way, so that the results obtained can be easily interpreted, and in an efficient way, so that the information contained in the composite indicator is maximal. In this paper, we propose a novel methodology based on the multicriteria reference point scheme. The decision maker can establish any number of reference levels for each indicator, and the final outcome can be interpreted in terms of the position with respect to these levels. Besides, two different aggregations are proposed: the weak indicator, allowing for full compensation among the single indicators, and the strong indicator, not allowing for any compensation. The joint visualization of both composite indicators provides valuable information that may be unnoticed using other existing approaches. The approach is illustrated using an example based on the EU-Regional Social Progress Index (EU-SPI).
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/17106
Keywords: Optimización matemática; Números índice (Economía); Composite indicators; Multiple objective programming; Multiple reference point scheme; Weak and strong indicators; Compensation